Studi Kasus Anak Usia 32 Bulan Dengan Gizi Kurang Dan Stunting Di Desa Cangguek Puskesmas Tanah Pasir Tahun 2023 - Intan Zuryani; Aditya Fajar Perkasa; Yolanda Restiani; Noviana Zara (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
Toddlerhood is also known as the "golden period". During this period, children also experience a critical period. One of the problems that often occurs is nutritional problems. Undernutrition is a condition of body weight according to age (BB/U) not in accordance with the age that should be. The next adverse impact that can be caused by nutritional problems in the first 1,000 days of birth (HPK) is the problem of stunting. Stunted children have an impact on cognitive abilities and long-term low immunity. Aceh Province is ranked 3rd in Indonesia for undernourished children under five at 10.7%. In addition, North Aceh District is ranked 4th for undernourished children under five at 13.6%. Stunting is caused by many factors, such as socioeconomics, maternal nutrition during pregnancy, infant morbidity, parental education and knowledge, and the mother's role in managing family meals. This case study discusses a 32-month-old toddler in Cangguek Village, conducted by observing the patient for 4 weeks with a home visit approach. The diagnosis of undernutrition and very short was based on the National Guidelines of the Indonesian Minister of Health No. 2 of 2020 concerning Pediatric Anthropometric Standards. After the diagnosis was made, the patient's grandmother was given education, supplementary feeding, and growth observation, and analyzed the factors that influenced the patient's condition. At the first visit, the patient's weight was 9.0 kg and the patient's TB was 83 cm. The conclusion of this study is that there are several determinants of undernutrition in patients including; economy, education level and knowledge of the patient's guardian, and wrong behavior.